PEMBINAAN IMAN ORANG MUDA KATOLIK DI PAROKI SANTA PERAWAN MARIA DIANGKAT KE SURGA KABANJAHE - Sitepu, Abdi Guna; Lumbanbatu, Johannes; Sinulingga, Aldi Alfrianza; Sihotang, Din Oloan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The Young Catholics (OMK) are individuals born and raised within the Catholic tradition from adolescence to early adulthood. Young people often undergo critical identity and faith development during this phase. OMK currently faces challenges and changes in an increasingly complex and dynamic world. Globalisation, technology, and social changes influence their perspectives on their faith values. The objective of this service is to provide spiritual guidance to OMK, enabling them to understand better and embrace their faith. Activities are conducted through lectures and materials on the Catholic faith, interspersed with games, group dynamics, songs and movements, and practical worship practices. The method used in analysing the results of this CommunityService is qualitative. The outcomes obtained reveal that through the service conducted, OMK has gained additional knowledge and understanding of the values of the Catholic faith.